SPECIFICITIES OF LEGAL LANGUAGE IN AUSTRIA - PALUSZEK, Karolina (Comparative Legilinguistics, 2016)
The article presents differences between legal language in Austria and in Germany[1]. Although German is the official language in both countries, their legal language differs significantly, especially in terms of legal terminology. Since the accession of Austria to European Union (1995) the provisions of EU law, drawn up in only one German version, were introduced in Austria. Austria therefore adopted EU legal order, the German version of which complied mainly with the legal language used in Germany[2]. In light of the above, a question of the impact of EU membership of Austria on the legal language in that country arises. It is necessary to examine whether the Austrian legal language differences are recognized and protected, or, on the contrary, the harmonization of law leads also to an unification of legal language. The conducted analysis of selected examples of Austrian, German and European legislation is an attempt to find answers to the aformentioned questions. From the perspective of non-native German speakers it is crucial to determine whether the specific terms of the Austrian legal language have been considered and appropriately marked in dictionaries;. for this purpose, the author has examined the inclusion of specific Austrian legal terms in Polish-German legal dictionaries. [1] The shorter, Polish version of the hereby article, entitled: “Tak samo czy inaczej? – terminologia języka prawnego w Niemczech i Austrii” had been published in: “Monitor Prawniczy 7/2014. Dodatek specjalny. I konferencja absolwentów szkół prawa niemieckiego Uniwersytetu Jagiellońskiego i Uniwersytetu Warszawskiego – materiały z konferencji”. [2] German language has the status of an official language in two other founding Member States of the European Economic Community – namely in Luxembug and Belgium.